Current panorama of temporomandibular disorders' field in Brazil - Naila Aparecida de Godoi MACHADO; Fernanda Ferruzzi LIMA; Paulo César Rodrigues CONTI (University of São Paulo, 2014)
In 2012, the recognition of the specialty of Temporomandibular Disorders and Orofacial Pain completed ten years. Given this scenario, it is extremely important to track the current situation of this field of knowledge in Brazil, specifically in the area of research and training. We hope to discuss the importance of the recognition of this specialty and the inclusion of these subjects in undergraduate programs in Dentistry. Objective: The objective of this study is to perform a bibliometric survey of researches regarding Temporomandibular Disorders and Orofacial Pain conducted in the country, determine the number of specialization courses in Orofacial Pain and the number of specialists in the field. Methods: The bibliometric survey was conducted based on the Dissertations Portal of Coordination for the Improvement of Higher education Personnel (CAPES) and on PubMed. The panorama of the field of Orofacial Pain and Temporomandibular disorders in Brazil was determined by searching on the website of the Brazilian Council of Dentistry. Results: We found 731 theses and dissertations with Temporomandibular Disorders and Orofacial Pain as the main subjects; 81 accredited/recognized Courses on Orofacial Pain and Temporomandibular Dysfunction completed; 8 accredited/recognized Specialization Courses on Orofacial Pain and Temporomandibular Dysfunction still in progress, and 1,064 registered specialists in Orofacial Pain and Temporomandibular Dysfunction in the Brazilian Council of Dentistry. Search in the PUBMED database yielded 576 articles published with the participation of Brazilian researchers as first authors and/or co-authors in the period from 2000 to 2013. From this amount, only 5 were published in Portuguese, while all the others were published in english. We can also notice that the number of published articles increases over time. Conclusion: The number of researches related to temporomandibular disorders has increased over the last ten years, as well as the number of specialization courses and the number of specialists, which represents a major breakthrough for this field of knowledge.